O Potencial de geração de energia elétrica de fonte eólica onshore e offshore no Estado do Ceará: uma análise financeira, social e ambiental - Grangeiro, Patrício Allyson Henrique Grangeiro (2012)
Electricity is considered an essential input for economic development of the country. The state of Ceará has a large onshore wind potential, which is being exploited by low investment costs and the broad lines of credit, and a potential further offshore, mainly in the mouth of the river Acaraú, which can lead the state to consolidate in the search for sustainable energy. The aim of this study was to evaluate the economic feasibility of implementing a wind farm in the state of Ceara, and socio-environmental impacts, for this analyzes based on changes in cash flows, and Ad Hoc method for the analysis environmental and social impacts were used. In addition to the wind farms are important in generating employment and income, financial analysis showed that the modality onshore, and cheaper, has financial viability if half the capital invested is financed, as the offshore model, despite having a higher potential , from the viewpoint of generating, has a low rate of return, which can remove investment for this type of wind farm.